Enrichment of bacterial strains for the biodegradation of diclofenac and carbamazepine from activated sludge. (May 2017) - Bessa, V.S.; Moreira, I.S.; Tiritan, M.E.; Castro, P.M.L.
Abstract: Carbamazepine and diclofenac have been pointed out as important markers for environmental pollution by pharmaceuticals. This study reports on the isolation of bacterial strains capable to degrade these micropollutants from activated sludge of a municipal wastewater treatment plant (WWTP). After selective enrichments, one strain able to degrade diclofenac and two strains able to degrade carbamazepine were isolated. The strains were identified by 16S rRNA gene sequencing. Strain Brevibacterium sp. D4 was able to biodegrade 35% of 10 mg L −1 of diclofenac as a sole carbon source; periodic feeding with acetate as a supplementary carbon source resulted in enhancing biodegradation to levels up to 90%, with a concomitant increase of the biodegradation rate. Strains Starkeya sp. C11 and Rhizobium sp. C12 were able to biodegrade 30% of 10 mg L −1 of carbamazepine as a sole carbon source; supplementation with acetate did not improve the biodegradation of carbamazepine by these strains. The activated sludge harboured bacteria capable to degrade the two top priority environmental contaminants and may be potentially useful for biotechnological applications. Highlights: Isolation of bacterial strains able to degrade the pharmaceuticals DCF and CBZ. Strains C11 and C12 were able to biodegrade 30% of 10 mg L −1 of CBZ as sole carbon source in 30 days. Strain D4 was able to degrade 35% of 10 mg L −1 of DCF as a sole carbon source in 30 days. The addition of acetate as supplementary carbon source enhanced DCF biodegradation up to 90%. This is the first report of a bacterium able to degrade DCF as a single strain.